94.1k views
5 votes
Solve for x: 5(x + 3) = 4(x − 3)

−18
−27
−3
−6

User Tapac
by
6.4k points

2 Answers

4 votes

Answer:


x = -27

Explanation:

First we simplify both sides of the equation. By using the distributive property of multiplication, we can rewrite


5 (x + 3) = 4(x - 3)

as


5x + 15 = 4x - 12

Now we subtract 4x from both sides:


5x + 15 - 4x = 4x - 12 - 4x

which gives us


x + 15 = -12

Now we subtract 15 from both sides:


x + 15 - 15 = -12 - 15

which gives us


x = -27

User Eaweb
by
6.3k points
2 votes

Answer:

x = - 27

Explanation:

Given

5(x + 3) = 4(x - 3) ← distribute parenthesis on both sides

5x + 15 = 4x - 12 ( subtract 4x from both sides )

x + 15 = - 12 ( subtract 15 from both sides )

x = - 27

User Ian A McElhenny
by
6.7k points